2012
DOI: 10.4014/jmb.1205.05047
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity of Pichia pastoris-Expressed Recombinant Envelope Protein of Japanese Encephalitis Virus

Abstract: Japanese encephalitis virus (JEV) envelope (E) protein holds great promise for use in the development of a recombinant vaccine. Purified recombinant E (rE) protein may be useful for numerous clinical applications; however, there are limitations in using the Escherichia coli expression system for producing high-quality rE protein. Therefore, in this study, the yeast expression system was used to generate the rE protein. For protein production using the yeast system, the full-length JEV E gene was cloned into Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Japanese encephalitis virus (JEV) envelope (E) protein expressed in P. pastoris was glycosylated. 71 The purity of E protein was greater than 95%. P. pastorisproduced recombinant E protein could stimulate immune responses that were capable of mediating significant protection against JEV infection.…”
Section: Recombinant Protein Subunit Vaccinesmentioning
confidence: 97%
“…Japanese encephalitis virus (JEV) envelope (E) protein expressed in P. pastoris was glycosylated. 71 The purity of E protein was greater than 95%. P. pastorisproduced recombinant E protein could stimulate immune responses that were capable of mediating significant protection against JEV infection.…”
Section: Recombinant Protein Subunit Vaccinesmentioning
confidence: 97%
“…Ammonium sulfate precipitation is often the first step in the purification of untagged recombinant proteins from yeast culture [37]. This approach allows to significantly concentrate the recombinant protein and get rid of some impurity proteins, while not disrupting the structure and properties of the target proteins [38,39]. It was experimentally found that recombinant ScGlu-3 is precipitated only when the concentration of ammonium sulfate reaches 50-65% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Neste sentido, cabe salientar que a reação de anticorpos bovinos específicos evidenciou uma maior reatividade à rBm86-CG obtida com sulfato de amônio em comparação a acetona e metanol. Além disso, a precipitação por sulfato de amônio permite que a amostra seja concentrada e submetida à purificação por cromatografia sem prejuízos a sua imunogenicidade (JEONG et al, 2016;KWON, 2012;LI et al, 2015;MA, 2013).…”
Section: Resultados E Discussão Precipitaçãounclassified